Investigating Factors Influencing Faculty Members’ Digital Competence for Capacity Building on Open and Distance Education in HEIs - Özlem Ozan; Yasin Özarslan (Open Praxis)
In order to create successful strategies for building adequate capacity by enhancing skills, we examined the impact of faculty members’ access to technology and support, perception of distance education, self-efficacy, and error management on their digital competence using a quantitative, descriptive, and correlational design. Data were collected through the DigiCompEdu (2021) survey, demographic questions, and measures of access to technology, perceptions of distance education, self-efficacy, and error management culture. The study was conducted at a foundation university on the Anatolian coast at the end of the 2022 Fall semester. Two hundred and seventy-two voluntary faculty members (53.3% female and 46.7% male) participated in the research. Descriptive statistics and inferential analyses were conducted to explore the relationships between digital competence and factors such as institutional support, prior experience, and personal characteristics (age, gender, teaching experience, digital experience). Findings provide insights into how these variables influence and predict digital competence, offering implications for professional development and institutional strategies to enhance digital skills among faculty. Self-efficacy was a significant factor affecting digital competence development, with a moderate positive relationship between access to technology and support and perception of distance education. The availability of technology and support can facilitate the adoption and use of distance education, enhancing faculty members’ confidence and efficacy in delivering distance education. The study also found that female faculty members have higher digital competence scores than males. The study also found that those with less than three years of digital experience tended to have lower scores. Furthermore, an error management culture, which focuses on learning and improvement, might facilitate a discussion of errors emerging by adapting new technologies instead of avoiding mistakes.